PERCERAIAN AKIBAT DISABILITAS MENTAL PERSPEKTIF SURAH AN-NUR AYAT 61 DAN HAK ASASI MANUSIA NASUTION - Setiyoningrum, Nurlaila Indah; Yasin, Raden Cecep Lukman (JURNAL AL-IJTIMAIYYAH, 2022)
Abstract: Divorce is the release of marriage bonds through the Religious Courts. Divorce with mental disabilities is a divorce carried out by the plaintiff against a defendant with a mental disability. The purpose of this study is to analyze divorce due to mental disability from the human rights perspective of Adnan Buyung Nasution and to analyze divorce from mental disability perspective from Surah An-Nur verse 61. This research method is a normative research with a case approach. The results of this study are that law enforcement on the rights of mental disabilities should also be supported by the government and law enforcement. Divorce for mental disabilities should not be granted, because it is increasingly painful and difficult to recover. In Surah An-Nur verse 61 it is stated that the rights of persons with mental disabilities are the same as normal humans, so that in treating persons with disabilities they are the same in the eyes of Allah and Islam strongly rejects discrimination against anyone.Keywords:  Divorce; Mental Disability; Human Rights. Abstrak: Perceraian merupakan terlepasnya ikatan pernikahan melalui peradilan Agama. Perceraian disabilitas mental merupakan perceraian yang dilakukan oleh penguggat terhadap tergugat yang penyandang disabilitas mental. Tujuan dalam penelitian ini yaitu untuk menganalisis perceraian akibat disbilitas mental perspektif hak asasi manusia Adnan Buyung Nasution dan untuk menganalisis perceraian disabilitas mental perspektif surah An-Nur ayat 61. Metode penelitian ini yaitu penelitian normatif dengan pendekatan kasus. Hasil dalam penelitian ini yaitu penegakan hukum terhadap hak-hak disabilitas mental sebaiknya didukung pula oleh pemerintah dan penegak hukum. Perceraian terhadap disabilitas mental sebaiknya tidak dikabulkan, sebab semakin menderita dan sukar untuk sembuh. Dalam surah An-Nur ayat 61 menyatakan bahwa hak penyandang disabilitas mental itu sama seperti manusia normal, sehingga dalam memperlakukan penyandang disabilitas-pun sama di mata Allah dan Islam sangat menolak diskriminasi terhadap siapapun.Kata Kunci: Perceraian; Disabilitas Mental; Hak Asasi Manusia.